Experimental study on grinding force in axial feed grinding of cemented carbide with diamond grinding wheel - Xiaoke REN; Hui HUANG; Zhenfa SU (Jin'gangshi yu moliao moju gongcheng, 2022)
In order to study the grinding force of diamond wheel in axial feed grinding of cemented carbide, the transformation models of horizontal grinding force, vertical grinding force, normal force and tangential force are established, the variation of grinding force under different process parameters was measured, the effects of process parameters on normal force, tangential force and axial force are analyzed, the empirical formula of grinding force is established. The results show that in the process of axial feed grinding, the maximum grinding force is the normal force, and the axial force is slightly less than the tangential force. The influence of grinding wheel linear speed on grinding force in three directions is roughly the same. The influence of grinding depth on grinding force in three directions is obviously different. The effect of feed rate on grinding force is not significant.